Cytolethal Distending Toxin Enhances Radiosensitivity in Prostate Cancer Cells by Regulating Autophagy - Lin, Hwai-Jeng; Liu, Hsin-Ho; Lin, Chia-Der; Kao, Min-Chuan; Chen, Yu-An; Chiang-Ni, Chuan; Jiang, Zhi-Pei; Huang, Mei-Zi; Lin, Chun-Jung; Lo, U-Ging; Lin, Li-Chiung; Lai, Cheng-Kuo; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Cytolethal distending toxin (CDT) produced by Campylobacter jejuni contains three subunits: CdtA, CdtB, and CdtC. Among these three toxin subunits, CdtB is the toxic moiety of CDT with DNase I activity, resulting in DNA double-strand breaks (DSB) and, consequently, cell cycle arrest at the G2/M stage and apoptosis. Radiation therapy is an effective modality for the treatment of localized prostate cancer (PCa). However, patients often develop radioresistance. Owing to its particular biochemical properties, we previously employed CdtB as a therapeutic agent for sensitizing radioresistant PCa cells to ionizing radiation (IR). In this study, we further demonstrated that CDT suppresses the IR-induced autophagy pathway in PCa cells by attenuating c-Myc expression and therefore sensitizes PCa cells to radiation. We further showed that CDT prevents the formation of autophagosomes via decreased high-mobility group box 1 (HMGB1) expression and the inhibition of acidic vesicular organelle (AVO) formation, which are associated with enhanced radiosensitivity in PCa cells. The results of this study reveal the detailed mechanism of CDT for the treatment of radioresistant PCa.